Service science : the foundations of service engineering and management - Qiu, Robin G. (Wiley, 2014)
"By relying on the recent development of service science, this book focuses on the science of implementing a service system throughout its lifecycle, spanning from service marketing, engineering, delivery, quality control, management, to further improvement. The author utilizes a combined theoretical and practical approach to discuss the field of service science. Driven by today's new business environment, including advanced computing and telecommunications, accelerated business globalization, increased automation, and highly on-demand and competitive innovations, emphasis on the service sector has evolved to sources of innovations, collaboration, and value co-creation to optimally and cost-effectively meet the needs of end users, i.e. satisfaction, success, and profitability. Leading and competitive services enabled by service systems are all remarkably delineated by people-centric, information-driven, e-oriented, and satisfaction/success-focused characteristics. Compared to the mature knowledge of goods-producing business practices, service science is developing innovative, new constructs for mathematical modeling, process design, marketing, resource-revenue-risk management, and strategy. The book contains six parts: the evolution of services; service systems physics; market and service design; engineering and operations; delivery and service quality; and sustainment and improvement. By eliminating theoretical dependencies of each part, the book can also be tailored for students with different backgrounds and expectations. As opposed to typical course books where problems and exercises are used to help readers digest covered subjects, this book heavily relies on case studies to show how the presented theories and design principles are applied in practice, making it more suitable for students and professionals to master the foundations of service management"--